Application of factor analysis in the typology of agriculture in Serbia - Mihajlović Ljiljana; Milinčić Miroljub; Vukoičić Danijela; Petrović Dragan (Glasnik Srpskog Geografskog Društva)
Factor analysis was used as a method for determining the types of agriculture in Serbia, which resulted in the synthesised and comprehensive data presented in the study. The subjectivity inherent in this method is mitigated by relevant statistical facts that clearly guide the course of factor analysis from the selection of parameters through rotation to the final results. Agricultural types were identified based on the development of specific factors and the administrative districts in which these factors dominate compared to others. It should be noted that the results obtained in this study cannot be considered relevant for further research, as the method of factor analysis proved to be inadequate for the small num-ber of input parameters and large spatial units such as administrative districts.